PENGARUH EKONOMI MAKRO DAN KINERJA MANAJEMEN TERHADAP RETURN ON ASSETS (ROA) PERBANKAN SYARIAH - ratih hastasari (Widya Cipta - Jurnal Sekretari dan Manajemen, 2019)
Profitability is used as one measure to find out whether the bank has run its function as well. Based on these things,  this research was conducted to test whether the macroeconomic factors such as Gross Domestic Bruto ( GDP), inflation and the real exchange rate (RER), and from the side of the bank management performance such as Non Performing Finance (NPF) and The Ratio of  Operational Expense to Operational Revenue (BOPO) have influence towards  Return On assets (ROA) of Islamic Banking. The Data used in this research was obtained from the financial statements of Otoritas Jasa Keuangan online publication (2011-2017). The sample used is purposive sampling,  these sample is 11 public bank of Sharia and 23 of Sharia business units. Data analysis technique that is used is multiple linear regression analysis and the first test performed classical assumptions to ensure the data has been BLUE. From the result of classical assumptions test is not found the variables that deviate from the classical assumptions test, this indicates that the data are qualified using regression analysis models. The results showed that the GDP influence positively and significantly  toward  ROA, inflation and real exchange rates (RER) do not  influence significantly toward  ROA, BOPO  influences negatively and significantly toward ROA, and NPF  influence significantly on ROA but having different direction with the hypothesis that has been proposed.